Credit Risk Management and Profitability of Japan Commercial Banks - Zhang, Wenwen (2014)
Credit risk management plays a significant role in the performance of banks, and they have become increasingly important in recent years. It can be regarded as an essential concept to decide the performance and survival of banks. This study will focus on the impact of credit risk management in Japanese commercial banks. The results are from strong balanced panel data set spanning 11 years around the period from 2002 to 2012. Fixed effect model and Ordinary Least Squares are used for the estimation. Return on Asset (ROA) is set as the dependent variable, and Capital Adequacy Ratio, Non-perming loans to gross loan ratio, natural logarithm of gross loans, Loan loss provision to non-perming loan ratio, GDPgrowth rate and inflation are set as independent variables. The 1990s financial crisis has influenced banks of Japan seriously, leading to a large number of NPLs and lower performance of banks. This lead to the credit risk emerged. During the research period, the results suggest a strong significant relationship between credit risk management and profitability, and find a significant effect of Basel II Pillar 1 on the performance of Japanese commercial banks. All the significant relation between ROA and independent variables revealing that the performance of Japanese commercial banks not only affected by the macroeconomic environment, but also influenced significantly by the credit risk management. The results indicate that Japanese banks are back. They have applied many measures to enhance their credit risk management, so they have write-off the NPLs and improve their performance. However, they still need to continue devoting themselves to improve their credit risk management.